Socio-economic Benefits of the EPS Sterna constellation at high latitudes - Perrels, Adriaan; Juhanko, Kaisa (Ilmatieteen laitos - Finnish Meteorological Institute, 2024)
This report presents a combined meteorological and economic study commissioned by EUMETSAT as part of the planning trajectory for the EPS-Sterna polar-orbiting satellite constellation. The focus of the study is on the foreseeable effects of EPS Sterna on meteorological forecasts and the resulting socioeconomic benefits, particularly regarding application at high latitudes, with emphasis on the Nordic countries. The study has an explorative character, hence the quantified estimates of benefits only indicate orders of magnitude for selected sectors. A more comprehensive assessment of expected benefits would necessitate a larger study. The report focuses on sectors for which significant benefits were expected, being civil aviation in Nordic countries (excluding Iceland) and wind turbine-based electricity production in the Nordpool area. For civil aviation, increased precision in forecast ing winterly precipitation enhances preparedness on airports, thereby reducing weather-related delays. The potential annual benefit for the aviation sector in the Nordic countries is estimated at approximately €5 million, with an additional €1 million in avoided travel time loss. The upscaled effect for aviation in Europe is estimated at around €15 million per year. In wind power production, timely identification of probable formation of ice and snow on turbine blades benefits the Nordic power market through smoother operations and cost savings. The expected annual benefits for society are approximately €15 million, growing to €27 million when considering growth in electricity use. Applying a satellite constellation lifetime of 12 years (2029–2040), the estimated cumulative benefits range from €240 million (using base year levels without expansion) to €495 million (using maximum values per sector). No discounting of benefits nor costs has been applied. Other sectors with potential benefits include construction, tourism, urban operational management, and more. A coarse assess ment for the Finnish building sector suggests expected ...